A Highly Sensitive and Selective Fluorescein-Based Cu2+ Probe and Its Bioimaging in Cell - Leng, Xin; She, Mengyao; Jin, Xilang; Chen, Jiao; Ma, Xuehao; Chen, Fulin; Li, Jianli; Yang, Bingqin (Frontiers in Nutrition, 2022)
Copper is a vital trace metal in human body which plays significant roles in amounts of physiological and pathological processes. The application of copper-selective probe has attracted great interests from environmental tests to life process research, yet few of sensitive Cu2+ tests based on on-site analysis have been reported. In this paper, a novel fluorescein-based fluorescent probe N4 was designed, synthesized, and characterized, which exhibited high selectivity and sensitivity to Cu2+ comparing with other metal ions in ethanol-water (1/1, v/v) solution. The probe N4 bonded with Cu2+ to facilitate the ring-opening, and an obvious new band at 525 nm in the fluorescence spectroscopy appeared, which could be used for naked-eye detection of Cu2+ within a broad pH range of 6-9. Meanwhile, a good linearity between the fluorescence intensity and the concentrations of Cu2+ ranged 0.1-1.5 eq was observed, and the limit of detection of N4 to Cu2+ was calculated to be as low as 1.20 µM. In addition, the interaction mode between N4 and Cu2+ was found to be 1:1 by the Job’s plot and mass experiment. Biological experiments showed that the probe N4 exhibited low biological toxicity and could be applied for Cu2+ imaging in living cells. The significant color shift associated with the production of the N4-Cu2+ complex at low micromolar concentrations under UV light, endows N4 with a promising probe for field testing of trace Cu2+ ions.